EVALUASI DAN PERENCANAAN MITIGASI RESIKO PROYEK PEMBANGUNAN JALUR GANDA KERETA API SEMARANG - BOJONEGORO - Aswan Munang; Faisal RM; Agus Mansur (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Calista Perkasa Mulia ( CPM ) ltd is a contracting company of the railway construction. In the project construction of double track railway Semarang- Bojonegoro period April 2012 to December 2013 , scheduling and risk management has not been implemented properly. It could been seen from the works that was not completed on schedule. Therefore, the purpose of this study was to design a project scheduling with precedence diagram method (PDM) and risk management. The results showed that one of the strategies which could be applied to anticipate the delay was the acceleration of the project. With this strategy the project could save as much as Rp730.638.742. Furthermore the risk of sources showed there were 28.21 % of technical risks, 46.15 % of not expected risk and 33.33 % unacceptable risk.